2021
DOI: 10.21203/rs.3.rs-325107/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

​Point-of-Care Ultrasound (POCUS) practices in the Helicopter Emergency Medical Services in Europe

Abstract: Background: The extent to which Point-of-care of ultrasound (POCUS) is used in different European helicopter EMS (HEMS) is unknown. We aimed to study the availability, perception, and future aspects of POCUS in the European HEMS. Methods: A survey about the use of POCUS in HEMS was conducted by a multinational steering expert committee and was carried out from November 30, 2020 to December 30, 2020 via an online web portal. Invitations for participation were sent via email to the medical directors of the Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
1
3
0
1
Order By: Relevance
“…The data suggests that the most common prehospital POCUS scans performed are cardiac ultrasound, lung ultrasound, vascular access and FAST. This correlates with previous studies conducted internationally which have shown FAST to be the most common ultrasound study undertaken by HEMS in Europe and elsewhere [17,20,21].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The data suggests that the most common prehospital POCUS scans performed are cardiac ultrasound, lung ultrasound, vascular access and FAST. This correlates with previous studies conducted internationally which have shown FAST to be the most common ultrasound study undertaken by HEMS in Europe and elsewhere [17,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…A 2014 North American cross-sectional convenience survey shows that 4.1% of Emergency Medical Services (EMS) incorporate ultrasonography within their prehospital care [10]. A one-month multinational survey in 2020 reported 75% of European HEMS services were using a POCUS assessment [17]. This comparison may not accurately reflect the current state of POCUS use due to lack of robust studies and data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…По данным общеевропейского онлайн опроса резидентов службы HEMS 25 стран, проведенного в 2020 г., УЗИ было доступно в 75 % организаций и использовалось у 15 % как травматологических пациентов, так и без травм. Самым используемым был расширен ный протокол FAST -он применялся в 77 % случаев [16].…”
Section: использование узи при санитарномедицинской эвакуации ургентн...unclassified